M. Syafe'i's Philosophy in the Meaning of Life and Its Implementation in Guidance and Counseling - Melva Syahrial; Yeni Karneli; Sufyarma Marsidin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
M. Syafe'i's philosophy is a philosophy that develops self-potential according to talents and interests. M. Syafe'i said that humans grow and develop according to their talents and interests. Develop the talents and interests they have and they will be great. The purpose of this study is to determine M. Syafe'i's Philosophy in the Meaning of Life and its Implementation in Guidance and Counseling. The method in this study is library research, focused on the description of M. Syafe'i's life journey, thoughts, and implementation of M. Syafe'i's philosophy in guidance and counseling. The results of this study are that M. Syafe'i's philosophy has the potential to make a significant contribution to guidance and counseling. This philosophy can help counselors develop a more individual-centered approach in helping their clients.